Effect of Anthocyanin-Rich Tart Cherry Extract on Inflammatory Mediators and Adipokines Involved in Type 2 Diabetes in a High Fat Diet Induced Obesity Mouse Model - Nemes, Andrea (Nutrients, 2019)
Male C57BL/6J mice were used to determine the possible therapeutic effects of our previously described tart cherry extract in a chronic obesity mouse model on metabolic parameters, glucose tolerance, inflammatory mediators, and antioxidant capacity. The control group received standard mouse chow, and the high fat control group was switched to a high fat diet and tap water supplemented with 5% sucrose. The high fat + anthocyanin group received the high fat and sucrose diet, but received the anthocyanin-rich tart cherry extract dissolved in their drinking water. After six weeks, an oral glucose tolerance test was performed, and the water-soluble antioxidant capacity (ACW), superoxide dismutase (SOD) activity, and the plasma levels of insulin, C-peptide, leptin, IL-6, MCP-1, adiponectin and resistin were measured. The high fat diet increased body weight, reduced glucose tolerance, and caused an elevation in leptin, IL-6, MCP-1, and resistin levels. Furthermore, antioxidant capacity was decreased with a significant elevation of SOD activity. Anthocyanin treatment failed to reverse the effects of the high fat diet on body weight and glucose tolerance, but significantly reduced the leptin and IL-6 levels. The tart cherry extract also made a significant enhancement in antioxidant capacity and SOD activity. Our results show that chronic anthocyanin intake has a potential to enhance redox status and alleviate inflammation associated with obesity.